2014
DOI: 10.1111/1478-9302.12050
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Inequality during the Great Recession in Greece

Abstract: The severe economic crisis that has been affecting Greece since 2009 is having an unprecedented impact in terms of job and income losses, and is widely perceived to have a comparably significant effect in terms of greater inequality and increased poverty. This article provides an early assessment of whether (and to what extent) the latter is the case. Specifically, it simulates the impact of the austerity (i.e. fiscal consolidation policies) and the recession (i.e. negative developments in the wider economy) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 18 publications
(29 reference statements)
0
23
1
1
Order By: Relevance
“…Unemployment rates for the under-30s are particularly high: 49.5% for individuals aged 15-24 and 39.7% for individuals aged 25-29 (Elstat, 2014). The number of people whose income fell below the 2009 poverty line (adjusted for inflation) reached 45% in 2013 (Matsaganis and Leventi, 2014). Overall, 1 in 7 people were below the extreme poverty threshold in 2013, compared to 1 in 45 in 2009, while poverty rates were higher among younger households in urban areas (Matsaganis and Leventi, 2014).…”
mentioning
confidence: 99%
“…Unemployment rates for the under-30s are particularly high: 49.5% for individuals aged 15-24 and 39.7% for individuals aged 25-29 (Elstat, 2014). The number of people whose income fell below the 2009 poverty line (adjusted for inflation) reached 45% in 2013 (Matsaganis and Leventi, 2014). Overall, 1 in 7 people were below the extreme poverty threshold in 2013, compared to 1 in 45 in 2009, while poverty rates were higher among younger households in urban areas (Matsaganis and Leventi, 2014).…”
mentioning
confidence: 99%
“…In the literature analysed, there is also no evidence of the emergency policies having a positive impact on job creation. In fact, various authors have found they have had a negative impact on worker rights, contributed to the destruction of employment (Miguélez et al, 2015), reduced the quality of employment, weakened collective bargaining (Torres, 2015), and increased poverty and inequality (Matsaganis and Leventi, 2014;Carmo and Cantante, 2015). Regarding the latter, important trends have emerged, particularly the reconfiguration of the traditional processes producing inequalities, with unemployment emerging as a new structural variable of social inequality, alongside of sex, age and education (Carmo and Cantante, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The large-scale arrival of refugees/asylum seekers have challenged Greeks to cope with a twofold crisis: the economic crisis as well as the refugee crisis. Concerning the economic crisis, in the last six years Greece has faced the most acute recession in its modern history with devastating socio-economic impacts on individuals' lives echoed in record unemployment and poverty rates (Matsaganis and Leventi 2014;OECD 2014). Since 2015, the country has been strained by both economic depression and the massive migration inflows of hundreds of thousands of refugees/asylum seekers.…”
Section: Discussionmentioning
confidence: 99%